The effect of telehealth and family planning service modules on interest in choosing long-term contraceptive methods for postpartum mothers in Cimahi City in 2021 - Tri Setiowati; Siti Nur Endah; Fitri Nurhayati (Science Midwifery, 2022)
The participation of long-term contraceptive method users is still not satisfactory. The pandemic condition and the lack of quality information about counseling caused this problem. Existing counseling guidelines have not been able to encourage women of childbearing age to choose long-term contraceptive methods. Telehealth which is carried out in a structured manner has the potential to increase interest in choosing long-term contraceptive methods, so the purpose of this study was to analyze the effect of telehealth on interest in choosing long-term contraceptive methods in postpartum women in Cimahi City. This type of research is a quasi-experimental. This study used a randomized pretest-posttest with a control group. Sampling was carried out by stratified random sampling on 50 postpartum mothers in Cimahi City. The selected samples were grouped in a simple random order so that there were 25 people for the treatment group and 25 people for the control group. The treatment group was given counseling using Telehealth while the control group was given standard counseling using the family planning module. The difference in the increase in interest in the treatment and control groups was tested by the Mann-Whitney test. The results showed a significant difference in interest scores after telehealth counseling was carried out between the treatment and control groups with a median interest of 17 (13-19) with a p value <0.05. In addition, telehealth influences the interest in choosing long-term contraceptive methods in postpartum women. The conclusion of this study, telehealth which is carried out in a structured manner can increase interest in choosing long-term contraceptive methods.